2021
DOI: 10.1093/neuros/nyaa540
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers for Glioma: A Review

Abstract: Accurate circulating biomarkers have potential clinical applications in population screening, tumor subclassification, monitoring tumor status, and the delivery of individualized treatments resulting from tumor genotyping. Recently, significant progress has been made within this field in several cancer types, but despite the many potential benefits, currently there is no validated circulating biomarker test for patients with glioma. A number of circulating factors have been examined, including circulating tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 107 publications
1
60
0
Order By: Relevance
“…For IDH-wide type GBM patients, the mutation of BRAF may benefit them while the co-alteration of EGFR/PTEN/CDKN2A and mutation of PIK3CA and H3K27M correlates with worse clinical outcomes ( Mirchia and Richardson, 2020 ; Umehara et al, 2019 ). Circulating biomarkers have also been developed in GBM because of their non-invasive potential ( Jelski and Mroczko, 2021 ; Kefayat et al, 2021 ), but the sensitivity and specificity are still problems to be solved ( Müller Bark et al, 2020 ; Raza et al, 2020 ; Jones et al, 2021 ). Additionally, there are still no clinically validated circulating biomarkers for GBM patients because of the limitation in blood-brain-barrier, low concentration, and their short half-life ( Müller Bark et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For IDH-wide type GBM patients, the mutation of BRAF may benefit them while the co-alteration of EGFR/PTEN/CDKN2A and mutation of PIK3CA and H3K27M correlates with worse clinical outcomes ( Mirchia and Richardson, 2020 ; Umehara et al, 2019 ). Circulating biomarkers have also been developed in GBM because of their non-invasive potential ( Jelski and Mroczko, 2021 ; Kefayat et al, 2021 ), but the sensitivity and specificity are still problems to be solved ( Müller Bark et al, 2020 ; Raza et al, 2020 ; Jones et al, 2021 ). Additionally, there are still no clinically validated circulating biomarkers for GBM patients because of the limitation in blood-brain-barrier, low concentration, and their short half-life ( Müller Bark et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the over 20 studies on miRNAs in gliomas showed variable, reasonable degrees of sensitivity and specificity, both often over 80% to 90%. The miRNAs relevant for brain tumors are often upregulated with a worse prognosis, but can also be downregulated compared to others: miR-10b, miR-15b, miR-15b-5p, miR-16-5p, miR-19b-3p, miR-20a-5b, miR-20a-5p, miR-21, miR-23a, miR-29, miR-106a-5p, miR-125, miR-128, miR-125, miR-125b, miR-128, miR-130-3p, miR-133a, miR-145-5p, miR-150, miR-181b-5p, miR-182, miR-182-5p, miR-197, miR-205, miR-208a-3p, miR-210, miR-221, miR-222, miR-222-3p, miR-223, miR-320, miR-320e, miR-328-3p, miR-339-5p, miR-340-5p, miR-374-3p, miR-376a, miR-376b, miR-376c, miR-454, miR-485-3p, miR-486, miR-486-5p, miR-497, miR-543, miR-548b-5b, and RNU6-1 [ 19 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Upregulation of miR-21 may serve as an early diagnostic but also as prognostic [ 63 ] and monitoring marker [ 81 ], whereas panels of different miRNAs were found to be potential markers for diagnostics and tumor grade, as well as prognostics [ 82 ].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…So far, breast cancer and prostate and colorectal carcinomas are the frontrunners in clinical applications. The limited number of reviews on liquid biopsy and brain tumors, often restricted to only specific subtypes [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], demonstrates that brain tumors are still out of the main focus of liquid biopsy applications; here, we summarize the fundamental challenges and recent developments, as well as provide our view of how to resolve these.…”
Section: Introductionmentioning
confidence: 99%
“…Many next-generation sequencing (NGS) and PCR-based methodologies have been utilized in CNS tumors to identify genetic markers, in particular, those of gliomas [ 52 ]. Droplet digital PCR (ddPCR) is a notable PCR-based technique for these applications as it is able to detect and quantify targets with low copies at high sensitivity.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…Approaches to improve the detection capabilities of ddPCR are being assessed including pre-amplifying cfDNA prior to ddPCR [ 61 ] and utilizing high affinity locked nucleic acid-enhanced probes to reduce the formation of secondary structures and stabilize amplification [ 60 ]. Sampling ctDNA through cerebrospinal fluid instead of plasma is an emerging approach to avoid the non-tumor contributors to plasma cfDNA while also accessing a biofluid with a higher ctDNA concentration [ 52 ]. Accessing ctDNA in CSF samples of brain tumor patients have shown significant promise in many CNS cancer types [ 62 , 63 , 64 ].…”
Section: Circulating Tumor Dnamentioning
confidence: 99%